BENEFIT COORPERATIONS AS A FORM OF SOCIAL BUSINESS: AN ASSESSMENT OF B CORP CERTIFIED BUSINESSES IN TURKEY (Third Sector Social Economic Review, 2017)
Benefit corporations are profit-oriented organizations, whose main purpose is to make social impact, are separated from other social enterprises by requirement of reporting their effects and certification. In this study, it is aimed to evaluate the situation in terms of benefit corporations that have been just recently discussed in the administrative context. Qualitative research has been carried out using primary and secondary data sources within the scope of B Corps in Turkey which are certified benefit companies by B Lab as an independent and non-profit organization, operating in 50 countries. It has been observed that benefit corporations in Turkey are embodying their mission with B Corp certificate and they think that they can provide guidance for benefit corporations. It seems that the corporations in question are aiming to use the B Corp certificate for developing a cooperation and attracting social impact investors. Coorporations’  experience indicates that legal regulations will be functional when benefit corporations become more prevalent in Turkey. With the prevalence, the awareness of benefit corporations is expected to increase.
Keywords: Social Business; Benefit Corporations; B Corp